Indonesia’s Roles in Myanmar’s Rohingya Crisis: Through the Lens of Public Diplomacy - Marlina, Revy; Kurniawan, Yoseph Wahyu; Rafly, Muhammad (Journal of Communication and Public Relations, 2024)
Myanmar's Rohingya crisis remains unresolved, with the Rohingya minority suffering human rights violations from the majority Buddhist Rakhine population, supported by the central government. As a result, many Rohingya have fled to neighboring countries like Thailand, India, Indonesia, Nepal, and others in the region (UN Refugees, 2022). Indonesia, a founding ASEAN member, believes ASEAN should address the Rohingya crisis, but ASEAN faces obstacles due to the non-intervention principle and differing ideologies and interests among member states. Concerned with the crisis since its emergence in 1948, Indonesia has intensified its peace-brokering efforts as the current ASEAN host, utilizing shuttle diplomacy and engaging key players in Myanmar. Resolving the conflict is significant for Indonesia, as it seeks to enhance its regional reputation and revive its influential role from the Soeharto era. Public diplomacy will be used in this paper by seeing the efforts of the Indonesian government, especially during President Jokowi's second term. As Joseph S. Nye said “soft power is the ability to affect others to obtain the outcomes one wants through attraction rather than coercion or payment,” we can see the Indonesia effort through shuttle diplomacy, implementation of the Five-Point Consensus on Myanmar, and humanitarian aid to solve this conflict.